Policy instruments for sustainable land management: the case of highland smallholders in Ethiopia - Shiferaw, Bekele; Holden, Stein (Wiley, 2000)
Degradation of land continues to pose a threat to future food production potential in many developing economies. Various approaches, mainly based on command-and-control policies, have been tried (with limited success) in the past to encourage adoption of erosion-control practices by farm households. High transactions costs and negative distributional impacts on the welfare of the poor limit the usefulness of standards and taxes for soil and water conservation. One innovative approach is the use of interlinked contracts which create positive incentives for land conservation. This study analyses the social efficiency of such policies for erosion-control in the Ethiopian highlands using a non-separable farm household model. Incentive contracts linked with conservation seem to be promising approaches for sustainable resource use in poor rural economies. This may suggest that conservation programs should give greater consideration to better fine-tuning and mix of policies that help achieve both economic and environmental objectives." -- Abstract.